Komunikasi Internal Kepala Sekolah Perempuan: Studi Kasus di SDIT Al Azhar Kota Kediri - Nurul Amalia; Zaenal Arifin (Jawda: Journal of Islamic Education Management, 2022)
This article reveals the communication of women leaders. When talking about female leaders, it will not be separated from the issue of gender stereotypes, many of which link the individual’s ability to lead with the biological aspects inherent in the leader, namely based on the sex differences between men and women. As result, the term gender inequality has emerged, which places women in unfavorable conditions. This type of research is qualitative and a case study as an approach. Data collection techniques used in-depth interviews with school principal informants, education personnel, school communities, and guardians of the students. The data analysis process uses a flow model which includes: data reduction, data presentation, and conclusion. This study found that the success of female leaders was influenced by their ability to communicate and appreciate professional relationships. Female leaders have more social orientation, an equal position, are quality based, care, and are more nurturing. In this case, women leaders often exercise leadership that is democratic and transformational